URGENSI ADAB DALAM BELAJAR DAN PEMBELAJARAN DI DUNIA PENDIDIKAN : - Sakila, Sakila; Masyithoh, Siti (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This journal article discusses the importance of etiquette in the context of teaching and learning in the world of education with a focus on developing and improving etiquette, both from the perspective of students and teachers. The research method used is library research, which integrates data and information from various related literature sources. The main discussion covers various aspects of etiquette, starting from student etiquette in the learning process, student etiquette when in the learning environment, to etiquette that must be shown to teachers, as well as etiquette that teachers must have in the learning process. Apart from that, the teacher's responsibility towards students is also highlighted in this article. The aim of this article is to increase understanding of the importance of etiquette in the educational context and to provide practical guidance for all parties involved in the teaching and learning process to improve and develop better etiquette. By paying attention to all the aspects discussed, it is hoped that a more productive, harmonious and constructive learning environment will be created. This environment will support optimal growth and positive character development for all individuals involved in the educational process.